WDR13 promotes the differentiation of bovine skeletal muscle‐derived satellite cells by affecting PI3K/AKT signaling. (27th May 2019) - Fu, Yuying; Li, Shuang; Tong, Huili; Li, Shufeng; Yan, Yunqin
Abstract: Muscle satellite cells are usually at rest, and when externally stimulated or regulated, they can be further differentiated by cell fusion to form new myotubes and muscle fibers. WD repeat domain 13 (WDR13) is highly conserved in vertebrates. Studies have shown that mice lacking the Wdr13 gene develop mild obesity, hyperinsulinemia, and increased islet β cell proliferation. However, the role of WDR13 in bovine cells is unclear. Here, we investigated the effect of WDR13 on bovine skeletal muscle‐derived satellite cells (MDSCs). We found that WDR13 was upregulated in bovine MDSCs using western blotting and immunofluorescence experiments. Moreover, activation and inhibition of WDR13 expression increased and decreased cell differentiation, respectively, suggesting that WDR13 promotes bovine MDSC differentiation. To further understand the mechanism of action of WDR13, we examined changes in the PI3K/AKT signaling pathway following WDR13 activation or inhibition. In addition, cells were treated with a phosphoinositide kinase 3 (PI3K) inhibitor, LY294004, to observe cell differentiation. The results showed that activation of WDR13 inhibited the PI3K/AKT signaling pathway and enhanced cell differentiation. These data suggest that WDR13 can promote the differentiation of bovine MDSCs by affecting the PI3K/AKT signaling pathway.